Allergen risk assessment: Food intake levels of the general population represent those of food allergic patients. (December 2020) - Blom, W. Marty; van Os-Medendorp, Harmieke; Bijlsma, Sabina; van Dijk, Anne; Kruizinga, Astrid G.; Rubingh, Carina; Michelsen-Huisman, Anouska D.; Knulst, André C.; Houben, Geert F.
Abstract: Unintentional intake of allergens through food products poses a daily risk for allergic patients. Models estimating the risk of reactions mostly use intake data from general population surveys. Our study evaluates the comparability of food intake levels in the general population to those in the food allergic population. Data were collected by a 24-h recall method on 2 non-consecutive days in 38 cow's milk and/or hen's egg and 35 peanut and/or tree nut allergic adult patients. All products were assigned to food groups previously developed for allergen risk assessment. Food intake distributions from the allergic populations and a matched sample from the Dutch National Food Consumption Survey were compared, and risk assessments were performed. Food intake data was obtained for 92% of the food groups. Comparison of the intake showed no statistically significant differences between either of the two allergic populations and the general population. Consequently, only small variations in estimated risks were found, that would not result in different risk management decisions. In conclusion, food intake data from the general population can be used for food allergen risk assessment and will not lead to a relevant under- or overestimation of the risk for the food allergic population. Highlights: The current study provides insight into the consumption amounts eaten by allergic patients. Food allergic patients and the general population eat equal quantities of food groups. Intake data from national food consumption surveys can be used for food allergen risk assessments.